Temporary Seismic Stations Installation and Building Damage Assessment of December 7th, 2016 Earthquake in Pidie Jaya, Aceh, Indonesia - Zulfakriza Z.; Andri D. Nugraha; M. Ridwan; Kadek P. Hendrawan; Muksin Umar; Muzli Muzli; Kemal Erbas; Daryono Daryono (Himpunan Ahli Geofisika Indonesia (HAGI), 2018)
A signicant Mw 6.5 earthquake occurred in Pidie Jaya, Aceh on December 7th, 2016. The event affected104 people death and more than 1000 people suered injuries due to the rubble of the building. Geologically, the region is composed by of Quaternary alluvial deposits. This is one of factor that amplication occurred in some area. On the other hand, an understanding of the source and mechanism of the earthquake needs to be done. A few days after the earthquake, we deployed 9 seismometers that covered the area of Pidie, Pidie Jaya and Bireuen. This experiment aims to record the aftershock and understanding of earthquake source and mechanism. In addition, we conducted building damage survey to know the pattern of distributionof building damage.